3-D motion trajectory measurement for the target through a multi-UAVs system. (30th November 2022) - Zhuge, Sheng; Xu, Xiangpeng; He, Yuwei; Lin, Bin; Gan, Shuwei; Zhang, Xiaohu
Abstract: High-accuracy and contactless measurement for the 3-D motion trajectory of the target is a challenging problem in photogrammetry. Our research proposes a measurement approach to estimate the motion of the target with the optical data captured by a system of multiple UAVs. In this paper, a fast-tracking approach is developed based on the motion continuity of the UAV, which enables tracking the feature points in image sequence with high precision. We established a simulation system for studying of factors affecting the measurement error of the proposed method. Moreover, the real robot tests were carried out to prove the feasibility and precision of the presented approach. The experiments show that, under the conditions that the observation radius is 5 m and the number of UAVs is 3, the RMSE of the motion trajectory measured by our method is 3.71 mm, and the RMSE of the size estimation of the target is 2.77 mm.